MINAT BERWIRAUSAHA SISWA KELAS XI SMKN 1 SUKADANA KABUPATEN KAYONG UTARA - Anggrayni, Rizky; Khosmas, F.Y.; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This thesis entitled "Analysis of Interest in Entrepreneurship of Students of Class XI SMK Negeri 1 Sukadana Kayong Utara Distric". The problem in this research is "how is the interest of entrepreneurship of students class XI SMK Negeri 1 Sukadana Kabupaten Kayong Utara Regency?" The focus of this research is entrepreneurship interest with indicators: (1) self confidence (2) Optimistic (3) Leadership (4) Flexibility (5) able in managing money (6) Imagination (7) able in planning (8) patience (9) explicit (10) enthusiasm (11) responsible (12) hardworking (13) the encouragement in a chieving something (14) integrity (15) self reliance (16) realism (17) organization (18) accuracy (19) tranquility (20) taking account of risk (21) physical healthy (22) communication with others (23) freedom (24) able in consorting (25) decision making. The population in the study is 174 with 63 sample students. Data collection tools this research was analyzed based on quantitative descriptive. The results showed that the interest of intrepereneurship of student s class XI SMK Negeri 1 Sukadana District has a percentage of 75,37% and the high category. From the results it can be concluded that the students have strong interests in entrepreneurship. Â Keywords: Interest, Entrepreneurship, Students